WHY SHOULD THE FACULTY ADOPT RECIPROCAL TEACHING AS PART OF THE MEDICAL CURRICULUM? - Khan, Muhammad Jaffar; Fatima, Sadia; Akhtar, Mehnaz; Owais, Muhammad (Journal of Ayub Medical College Abbottabad, 2016)
Understanding the text is crucial to achieve depth in understanding of complex concepts for students at all levels of education for whom English is not their first language. Reciprocal teaching is an instructional activity that stimulate learning through a dialogue between teachers and students regarding segments of text. The process of summarizing, question-generating, clarifying and predicting allows the gaps to be recognised and filled by the student, who is in control of the learning process and able to analyse and reflect upon the reading material. Whereas reciprocal teaching has been applied at school and college level, little is known about its effectiveness in medical education. Incorporating reciprocal teaching in early years of medical education such as reading the literature and summarizing the flow of information in the study of integrated body systems could be an area to explore. Feasibility exercises and systematic validation studies are required to confirm authors’ assertion. Keywords: Reciprocal teaching; Curriculum, Adult education; Adult learning